What is the relationship between high-density lipoprotein cholesterol and the extension of coronary heart disease?. (25th November 2020) - Santos, M.R; Pereira, A; Mendonca, F; Sousa, J.A; Temtem, M; Monteiro, J.P; Sousa, A.C; Freitas, S; Rodrigues, M; Ornelas, I; Mendonca, M.I; Palma Dos Reis, R; et al.
Abstract: Introduction: Coronary atherosclerosis is an important pathophysiological mechanism in the development of coronary artery disease (CAD). While it has been proven via multiple studies that elevated levels of low-density lipoprotein (LDL) contribute to the development of atherosclerosis, high-density lipoprotein (HDL) is widely thought to have atheroprotective effects. Multiple epidemiologic studies have given the idea that high HDL levels protect against CAD, however, other trials also shown that its benefit can be paradoxical. Objective: To evaluate the relationship between HDL levels and the extent of CAD (one vessel vs multivessel disease) in coronary artery patients. Materials and methods: Study analyses of 1676 patients selected from GENEMACOR study population, with at least one >75% coronary stenosis by angiography (median age 53.3±7.9 years, 78.6% male, median HDL 43.0±11.1 mg/dL). Population was divided according to the HDL level quartiles (1st quartile HDL <35.3 mg/dL; 2nd quartile HDL 35.3–42 mg/dL; 3rd quartile HDL 42–49 mg/dL; 4th quartile HDL >49 mg/dL). Population of the 1st and 4th quartiles (825 patients, median age of 53.3±7.9 years and 78.7% male) were adjudicated and prospectively followed-up by 5.0±4.8 years. χ 2 and T student tests were used to analyze the demographic, laboratorial, angiographic and anthropometric characteristics of the population according to HDL level. Results: 420 (50.9%) patients were included in the 1st quartile group (median age 53.2±7.9 years, 85.7% men) and 405 (49.1%) patients were included in the 4th quartile group (median age 53.4±8.0 years, 71.4% men). In our population, lower levels of HDL were associated with increased risk of multivessel coronary disease (OR 1.63, 95% CI 1.23–2.14, p 0.001). Conclusion: Despite uncertainties about HDL benefit, in our population a higer level of HDL was associated with a shortest extent of coronary artery disease. We conclude that higher levels of HDL can be considered protective in coronary patients, and strategies to increase HDL levels may indeed translate in improved outcomes in CAD disease. Funding Acknowledgement: Type of funding source: None